Optimizing crop quality and yield: asessing the impact of integrated potassium management on Chinese cabbage (Brassica rapa L. subsp. chinensis) - Choudhary, Mahendra; Kumar, Sourabh; Onte, Santosh; Meena, Vijendra Kumar; Malakar, Dhruba; Garg, Kamal; Kumar, Sanjeev; Rajawat, Mahendra Vikram Singh; Awasthi, Mukesh Kumar; Giri, Balendu Shekher; Jaiswal, Durgesh Kumar; Dhar, Shiva; et al. (Elsevier, 2024)
Potassium, a pivotal macronutrient essential for growth, development, and crop yield, serves as a critical determinant of soil productivity. Its depletion disrupts the equilibrium of soil nutrients, prompting an investigation into integrated potassium management strategies to address this challenge. A field experiment was conducted during the winter season of 2020 using a randomized complete block design, with eight treatments, each replicated three times in Chinese cabbage (Brassica rapa L. subsp. chinensis). These treatments comprised standard (100 %) and reduced (75 % and 50 %) rates of the recommended dose of potassium (RDK) via muriate of potash (MOP). Variations in the inclusion and exclusion of plant growth-promoting rhizobacteria (PGPR), farmyard manure (FYM) as 25 % of the potassium recommendation, and foliar spray of nano potash were systematically implemented. Findings unequivocally demonstrated that the treatmentT8, involving 100 % RDK +25 % K through FYM + PGPR + nano K fertilizer spray at 25 and 40 DAS, yielded significant improvements in both green fodder (64.0 t ha−1) and dry fodder (7.87 t ha−1).Moreover, T8 exhibited the highest values for total ash (8.75 %), total ash yield (68.9 ± 2.88 kg ha−1), ether extract (2.85 %), ether extract yield (22.4 ± 0.88 kg ha−1), crude protein (9.71 %), and total crude protein yield (76.4 ± 3.21 kg ha−1). Conversely, a marked reduction was observed in various fiber components and carbohydrate fractions upon application of the T8 treatment. The lowest values of yield, crude protein content, total ash ether extract were recorded in treatment T1 (control) applied with no potassium. This investigation underscores the inadequacy of the recommended potassium dose in achieving optimal productivity, necessitating a re-evaluation of potassium fertilization levels. The integrated approach involving FYM, PGPR, and nano potash, coupled with the recommended potassium dose through MOP, emerges as a promising avenue for augmenting both yield and quality parameters in Chinese cabbage.